4G interactive heterogeneous telecommunication system (IHTS) - Burtovyi, Sergii; Sunduchkov, K. S. (Видавництво Львівської політехніки, 2010)
In this paper the possible variant of IHTS topology is given.
Keywords: interactive; telecommunication system; optical fiber; satellite radio channel